Social Cohesion, resilience and peace building between host population and Rohingya Refugee Community in Cox’s Bazar, Bangladesh - Olney, Jessica; Badiuzzaman, Muhammad; Hoque, Mohammad Azizul (Brac University, 2022)
In August 2017 Myanmar authorities unleashed systematic violence on the Rohingya community of Northern Rakhine State. Hundred of thousands of Rohingya were affected and an unknown number were killed, resulting in nearly a million people fleeing their homeland and taking shelter in the neighboring country of Bangladesh. Hosting such a large number of refugees has had significant impacts on the host population of Cox’s Bazar. These impacts have led to a lack of social cohesion and negatively affected the potential for inter-communal harmony between the two communities. A study was undertaken by BRAC University Centre for Peace and Justice (CPJ) between January to April 2019 to identify factors affecting social cohesion, resilience and peace building between the host and Rohingya refugee communities. The study consisted of a series of consultations conducted in order to compile the perspectives of different groups of host community stakeholders. Participant included local villagers (men, women and youth) living adjacent to the camps; local government representatives; community elders; religious and ethnic minority leaders; and representatives from NGOs, educational institutions, and civil society organizations (CSOs). The consultations included thirteen focus group discussions (FGDs), five key informant interviews (KIIs), one validation session of findings, and one dissemination workshop. The dissemination workshop was organized to share key findings with stakeholders who are potential catalysts in promoting stability in the region. The aim was to draw out their recommendations on ways to strengthen social cohesion and resilience in the region.